2007
DOI: 10.1016/j.jpedsurg.2007.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Familial intussusception

Abstract: We concluded that hereditary predisposition, such as anatomical basis, may be considered as an etiological factor in many cases of idiopathic intussusception. In these predisposed families, if they have inducements such as viral infections as the acquired agents, intussusception will occur very easily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…On the other hand, a genetic predisposition has been suggested in families (3). There was estimated that the risk to siblings is about 5-20 times more than that for the general population in literature (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a genetic predisposition has been suggested in families (3). There was estimated that the risk to siblings is about 5-20 times more than that for the general population in literature (4).…”
Section: Discussionmentioning
confidence: 99%
“…Intussusception is a well-known disease, and one of the most frequent causes of acute bowel obstruction in children aged 3-18 months, with an incidence of 0.1-0.4% of live births. Although idiopathic intussusception has not been considered a genetic disease, it has also been reported in families and relatives (1)(2)(3)(4). Herein, we present the first case report in the English literature of simultaneous occurring intussusception in monozygotic twins.…”
Section: Introductionmentioning
confidence: 89%
“…McLaughlin (1948) proposed that ileocolic and ileocecal are most common because of the disproportionate growth between the colon and the ileum in infancy, both being of similar size at birth. The disproportion between the protruding ileocecal valve and the ileum in infancy may form the apex of an ileocecal intussusception (Cooke and Lewis, 1960;Oshio et al, 2007). Perrin and Lindsay (1921) studied the anatomy of the cecum and ileum in children less than 1 year of age compared with older children and found that younger children have a more prominent valve with more lymph tissue congregated nearby.…”
Section: Anatomymentioning
confidence: 99%
“…In children, a mobile cecum and malrotation could allow for the ileum to pass into the cecum and then the cecum to pass into the colon (Tatekawa et al, 1998;Stringer and Babyn, 2000;Oshio et al, 2007). The pairing of malrotation and intussusception is called Waugh's syndrome (Brereton, 1986;Breckon and Hadley, 2000;Inan et al, 2004).…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation